2015
DOI: 10.1016/j.yebeh.2015.01.011
|View full text |Cite
|
Sign up to set email alerts
|

Health behaviors among people with epilepsy—Results from the 2010 National Health Interview Survey

Abstract: Objectives This study aimed to estimate and compare the prevalence of selected health behavior—alcohol use, cigarette smoking, physical activity, and sufficient sleep—between people with and without a history of epilepsy in a large, nationally representative sample in the United States. Methods We used data from the 2010 cross-sectional National Health Interview Survey (NHIS) to compare the prevalence of each health behavior for people with and without epilepsy while adjusting for sex, age, race/ethnicity, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(37 citation statements)
references
References 30 publications
1
34
1
1
Order By: Relevance
“…17,19 This study has several limitations that should be acknowledged including the modest sample size, limited but pertinent scope of risk factors, cross-sectional research design, and circumscribed knowledge of lifetime AED use and compliance. 17,19 This study has several limitations that should be acknowledged including the modest sample size, limited but pertinent scope of risk factors, cross-sectional research design, and circumscribed knowledge of lifetime AED use and compliance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…17,19 This study has several limitations that should be acknowledged including the modest sample size, limited but pertinent scope of risk factors, cross-sectional research design, and circumscribed knowledge of lifetime AED use and compliance. 17,19 This study has several limitations that should be acknowledged including the modest sample size, limited but pertinent scope of risk factors, cross-sectional research design, and circumscribed knowledge of lifetime AED use and compliance.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, epidemiologic research has documented a number of health, lifestyle, and socioeconomic factors (e.g., decreased physical activity, sleep, social interaction) that could lead to issues that should also be considered going forward. 17,19 This study has several limitations that should be acknowledged including the modest sample size, limited but pertinent scope of risk factors, cross-sectional research design, and circumscribed knowledge of lifetime AED use and compliance.…”
Section: Discussionmentioning
confidence: 99%
“…Recent qualitative research has confirmed these benefits of exercise, with participants voicing that exercise increases their physical health, decreases stress levels, increases self-esteem, positively impacts mood, and improves QoL overall [4,5]. Although both qualitative and quantitative research have presented the positive impact of sports and exercise for a person with epilepsy [1-3, 5, 6], the prevalence of regular exercise for a person with epilepsy is lower compared to the general public [7], as there are still common barriers (both physical and psychosocial) that prevent many PWE from feeling the benefits of exercise [4,5,8]. The main barriers to sports and exercise reported are fear of the seizure occurring [4,8], fear of seizure-related injuries [9], stigma [5,10] and incorrect advice from medical professionals [4,5,11,12,13].…”
Section: Introductionmentioning
confidence: 99%
“…36 The 2010 National Health Survey in the United States reported that in preceding week only 39% of people with epilepsy had walked for ≥10 minutes per day, compared to 50% of the general population. 39 Not surprisingly, another study indicated that compared with siblings, adolescents with epilepsy were less likely to be involved in sport groups or engaged in physical activity, and more likely to be overweight and obese. 40 On the positive side, people with epilepsy in Arizona who had regular physical activities had fewer activity limited days.…”
Section: Other Activities That May Improve Transition/transfer Successmentioning
confidence: 99%